If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11a + 18b + 6C + 4C + -4B + -2A = 0 Reorder the terms: -2A + -4B + 6C + 4C + 11a + 18b = 0 Combine like terms: 6C + 4C = 10C -2A + -4B + 10C + 11a + 18b = 0 Solving -2A + -4B + 10C + 11a + 18b = 0 Solving for variable 'A'. Move all terms containing A to the left, all other terms to the right. Add '4B' to each side of the equation. -2A + -4B + 10C + 11a + 4B + 18b = 0 + 4B Reorder the terms: -2A + -4B + 4B + 10C + 11a + 18b = 0 + 4B Combine like terms: -4B + 4B = 0 -2A + 0 + 10C + 11a + 18b = 0 + 4B -2A + 10C + 11a + 18b = 0 + 4B Remove the zero: -2A + 10C + 11a + 18b = 4B Add '-10C' to each side of the equation. -2A + 10C + 11a + -10C + 18b = 4B + -10C Reorder the terms: -2A + 10C + -10C + 11a + 18b = 4B + -10C Combine like terms: 10C + -10C = 0 -2A + 0 + 11a + 18b = 4B + -10C -2A + 11a + 18b = 4B + -10C Add '-11a' to each side of the equation. -2A + 11a + -11a + 18b = 4B + -10C + -11a Combine like terms: 11a + -11a = 0 -2A + 0 + 18b = 4B + -10C + -11a -2A + 18b = 4B + -10C + -11a Add '-18b' to each side of the equation. -2A + 18b + -18b = 4B + -10C + -11a + -18b Combine like terms: 18b + -18b = 0 -2A + 0 = 4B + -10C + -11a + -18b -2A = 4B + -10C + -11a + -18b Divide each side by '-2'. A = -2B + 5C + 5.5a + 9b Simplifying A = -2B + 5C + 5.5a + 9b
| 8x+17=25 | | 15-(y+6)=16 | | 2(4a+2)-3(2a-4)= | | -3(x-5)+2(4x-8)=12 | | 2x^2+3x=200 | | 0.5x^2+3x-36=0 | | 2xy-5yx+7= | | 180(3.14)=2(3.14)*10 | | 28=4v-8 | | 60+20x=96+11x | | 7(8)-3(-8)=5 | | 9z-90=-4z-10 | | x+3=-3+x-2+8 | | y=-3(8)+2 | | y=-3(8)x+2 | | y=-3(0)x+2 | | 2(8s+2)-6s=2(5s+4)-13 | | 7x+17=4x+1 | | 12(3x+3)-5(2x-3)=6x-49 | | 0.55x+0.05(10-x)=0.10(-25) | | 9x+10-6x=6x+40 | | -2(x-8)=4(x+1) | | 10x+7+5x=7x+31 | | (t+9)+(4t-15)= | | 17x+4=10-45 | | 12y+8=5y-5 | | 5(-4)-4y=20 | | (Gx)=6x^2-224x+4941 | | solvex^3-2x-1.5=0 | | x^3-2x-1.5=0 | | 172-6x=5x+18# | | r^2-10r+6=0 |